2010
DOI: 10.1111/j.1439-0523.2009.01658.x
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin-induced mesocotyl elongation in deep-sowing tolerant maize inbred line 3681-4

Abstract: In order to elucidate the molecular mechanism of gibberellin (GA)-induced mesocotyl elongation, gene expression profiling analyses were performed in a deep-sowing tolerant maize inbred line 3681-4. Gene expression studies combining Affymetrix GeneChip analysis and Realtime PCR were employed to determine the molecular mechanism underlying GA promotion of maize mesocotyl elongation. These studies showed that a mount of genes, such as the GA receptor GID1, the transcriptional factor MYB, and the genes encoding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 20 publications
6
33
0
Order By: Relevance
“…However, its expression was upregulated as germination time went on at 0 cm sowing depth. The results suggest the key factor for seed germination of maize in deep soil (Troyer, 1997;Zhao et al, 2010). However, there were no obvious laws of ZmMYB59 expression in plumules or roots.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, its expression was upregulated as germination time went on at 0 cm sowing depth. The results suggest the key factor for seed germination of maize in deep soil (Troyer, 1997;Zhao et al, 2010). However, there were no obvious laws of ZmMYB59 expression in plumules or roots.…”
Section: Discussionmentioning
confidence: 87%
“…The results coincide with the trends of ZmMYB59 expression under the conditions of deep‐sowing. As is well known, mesocotyl elongation is the key factor for seed germination of maize in deep soil (Troyer, ; Zhao et al., ). However, there were no obvious laws of ZmMYB59 expression in plumules or roots.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nonetheless, the contributions of MYB transcription factors during seed germination have not yet been functionally characterized. In our previous study, to elucidate the molecular mechanisms of maize seed germination at 20 cm sowing depth, gene expression of mesocotyl was analyzed by Affymetrix GeneChip [15]. The results demonstrated that there was the highest expression level of MYB genes, accounting for 8.15% of total number of transcription factor family [15].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, a new MYB transcription factor gene named ZmMYB59, was cloned from the B73 inbred line. Affymetrix GeneChip was employed to analyze the gene expression patterns of mesocotyl tissue during maize seed germination at 20 cm sowing depth, indicating that MYB genes were significantly expressed [15]. Thereafter, Real-Time PCR showed the expression of ZmMYB59 in maize mesocotyl was fairly down-regulated during seed germination [16].…”
Section: Introductionmentioning
confidence: 99%